TECHNICAL EFFICIENCY OF TABLE SIZE CATFISH PRODUCTION IN KAINJI LAKE BASIN, NIGERIA - ILESANMI, Z. F; IFEJIKA, P.I.; MUHAMMAD-LAWAL, A.; OMEJE, J.E.; IFEJIKA, L.I.; I. A. , ENWELU (Nigerian Journal of Fisheries, 2023)
The study investigated the technical efficiency of catfish table size production under intensive system among cluster fish farmers in Kainji Lake Basin. Multistage sampling procedure was deployed to select 120 respondents for the study from three clusters namely Monai, Fakun and New Bussa in 2020. Primary data were collected with semi structured questionnaire and analyzed using descriptive statistics and Cobb-Douglas regression analysis to determine technical efficiency of table size catfish production in the study area. Findings showed that the catfish table size entrepreneurs are mostly men (86%) with mean age of 38 years. Majority (96%) are marriedand educated (72.5%) with 40.83% having household size of 4-5 persons with good fish farming experience (x=5years). Majority (99%) use earthen ponds while 94% farm hybrid (hetero-clarias) species. Total number of fingerlings was 970,600 stocked in a 47,493m2 size of ponds and fed with 741,060kg feed. The significant production efficiency factors were type of ponds, farming experience, household size, years of education, marital status, age, size of ponds and labour. Therefore, improving production efficiency in the area requires adherence to stocking density, mentoring young fish farmers, and adoption of best aquaculture practices. In addition, post fingerlings should be stocked in earthen ponds supported with technical knowledge through training, embracing agribusiness management and marketing principles to ensure profitable return on enterprise and sustainability as well as cooperative approach to overcome common issue.